2022
DOI: 10.3390/ijms23137218
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Conditions Responsible for Methylmercury-Mediated Neurotoxicity

Abstract: Methylmercury (MeHg) is a widely known environmental pollutant that causes severe neurotoxicity. MeHg-induced neurotoxicity depends on various cellular conditions, including differences in the characteristics of tissues and cells, exposure age (fetal, childhood, or adulthood), and exposure levels. Research has highlighted the importance of oxidative stress in the pathogenesis of MeHg-induced toxicity and the site- and cell-specific nature of MeHg-induced neurotoxicity. The cerebellar granule cells and deeper l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 55 publications
(78 reference statements)
0
9
0
1
Order By: Relevance
“…Our previous studies revealed that intracellular kinases and neuronal activation play important roles in MeHg neurotoxicity. The p38 MAPK‐CREB pathway plays a central role in MeHg neurotoxicity, ultimately leading to neuronal death via subsequent neuronal activation 44,45 . First, we examined the steady‐state activation of various kinases and neurons, and found that p44/42 MAPKs were approximately 2‐fold more active in HiNs than in CCNs, although no differences were observed in the activation of other kinases and neurons (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies revealed that intracellular kinases and neuronal activation play important roles in MeHg neurotoxicity. The p38 MAPK‐CREB pathway plays a central role in MeHg neurotoxicity, ultimately leading to neuronal death via subsequent neuronal activation 44,45 . First, we examined the steady‐state activation of various kinases and neurons, and found that p44/42 MAPKs were approximately 2‐fold more active in HiNs than in CCNs, although no differences were observed in the activation of other kinases and neurons (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The p38 MAPK-CREB pathway plays a central role in MeHg neurotoxicity, ultimately leading to neuronal death via subsequent neuronal activation. 44,45 First, we examined the steadystate activation of various kinases and neurons, and found that p44/42 MAPKs were approximately 2-fold more active in HiNs than in CCNs, although no differences were observed in the activation of other kinases and neurons (Figure 5). Next, we examined the time course and dose dependence of the activation of various kinases and neurons following MeHg exposure.…”
Section: Discussionmentioning
confidence: 99%
“…MeHg, a well-known neurotoxin, causes pathological changes, not due to its accumulation in tissues, but due to the severe and irreversible neurotoxicity it induces depending on the cellular environment, neurotransmitter balance, and developmental stage. 22 Developmental markers are mainly used to assess early prenatal or postnatal effects. In this study, there were no differences between the groups in terms of pinna unfolding, tooth eruption, and eye opening.…”
Section: Discussionmentioning
confidence: 99%
“…MeHg, a well‐known neurotoxin, causes pathological changes, not due to its accumulation in tissues, but due to the severe and irreversible neurotoxicity it induces depending on the cellular environment, neurotransmitter balance, and developmental stage 22 . RSV has been investigated as an anti‐aging, antioxidant, anti‐inflammatory, and neuroprotective agent in vitro and in vivo; however, the anti‐MeHg neurotoxicity mechanisms of RSV have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Compared to Hg 2+ , CH 3 Hg + is lipid-soluble and crosses biological membranes easily, causing damage to the kidneys, especially to the renal tubular epithelial cells in the proximal part of the kidneys, 11,12 when it enters the body of humans and animals through fish and shrimps. 13 In addition, mercury can cause immune dysfunction 14 and damage cerebral nerves 15,16 and endocrine systems. 17 As such, rapid and accurate detection of mercury is critical for monitoring the distribution and evolution of mercury species.…”
Section: Introductionmentioning
confidence: 99%